A Luminescent Steroid-based Organogel: ON-OFF Photoswitching by Dopant Interplay and Templated Synthesis of Fluorescent Nanoparticles - Edelsztein, Valeria Carolina (2012)
The modulation of the fluorescence emission of a perylene dye between ON and OFF states was achieved with high efficiency by means of a diarylethene photochromic compound in an organogel medium. Fluorescent gels were prepared from a steroidal low molecular weight organogelator doped with the perylene fluorophore. The compatibility of the photochromic compound in this medium and the non-destructive readout capability was demonstrated. The dye doped organogel was further used as template as an innovative method to grow fluorescent silica spherical nanoparticles with physically and chemically admixed perylene dye.